Usefulness of a Nonsuture Closure Device in Patients Undergoing Diagnostic Coronary and Peripheral Angiography - Owens, John T.; Bhatty, Shaun; Donovan, Robert J.; Tordini, Andrea; Danyi, Peter; Patel, Kalpesh; Wegelin, Jacob A.; Jovin, Ion S. (International Journal of Angiology, 2017)
Vascular access site complications can follow diagnostic coronary and peripheral angiography. We compared the complication rates of the Catalyst vascular closure device, with the complication rates after manual compression in patients undergoing diagnostic angiographic procedures via femoral access. We studied 1,470 predominantly male patients undergoing diagnostic coronary and peripheral angiography. Catalyst closure devices were used in 436 (29.7%) patients and manual compression was used in 1,034 (70.3%) patients. The former were allowed to ambulate after 2 hours, while the latter were allowed to ambulate after 6 hours. Major complications occurred in 4 (0.9%) patients who had a Catalyst device and in 14 (1.4%) patients who had manual compression (odds ratio [OR]: 0.67, 95% confidence interval [CI]: 0.22–2.1, p = 0.49). Any complications occurred in 51 (11.7%) patients who had a Catalyst closure device and in 64 (6.2%) patients who had manual compression (OR: 2, CI: 1.4–3, p < 0.01). After adjustment for other variables and for a propensity score reflecting the probability to receive the closure device, the association of major complications with the use of the closure device remained not significant (OR: 0.54, 95% CI: 0.17–1.7, p = 0.29), while the association of any complications with the use of the Catalyst device remained significant (OR: 1.9, 95% CI: 1.3–2.9, p < 0.01). The Catalyst device was not associated with an increased risk of major groin complications but was associated with an increased risk of any complications compared with manual compression. Patients receiving the closure device ambulated sooner.
Keywords: closure device; groin access complications; hematoma; bleeding